Intentionality and transcendence as core components of the spiritual-religious experience. A review of the question from the phenomenology of Dietrich von Hildebrand and the psychology of religion of Kenneth Pargament - Gargiulo, María Teresa (2022)
In psycho-clinical research, the notion of spirituality acquires a semantic plurality. This equivocal and ambiguous connotation that characterizes this term represents an obstacle to research designs’ epistemic and methodological validity, recognized as the threat to construct validity. To overcome this difficulty, we introduce the notions of intentionality and transcendence from Dietrich von Hildebrand’s phenomenology insofar as these can account for the specific element of the spiritual-religious phenomenon and discriminate it from the other phenomena or variables that may be included under the notion of spirituality. This conceptual elucidation task allows evaluating the legitimacy of the variable selection process and establishing why they are or are not representatives of the phenomenon of spiritual-religious experience. Along the same lines, we believe that Hildebrand’s efforts to delimit a philosophical notion of spirituality are clearly articulated in the definitional approach by the psychologist of religion, Kenneth Pargament.